Sliding Window Evaluation of the Wiener-Hopf Equation - Kraker, Alfred; Csuka, Barna; Kollar, Zsolt (Společnost pro radioelektronické inženýrství, 2020)
This paper presents an efficient method for solving the Wiener-Hopf equation in a sliding window by calculating the correlation matrices recursively. Furthermore, a novel algorithm is introduced for evaluating the inverse of the auto-correlation matrix - the Recursion with Splitting the Correlation matrix into 4 Blocks for Inversion - which can significantly reduce the computational requirements. The presented procedure is optimized for special cases to achieve an efficient implementation which allows faster rel-time signal processing or to reduce the response time - e.g. the latency -- by distributing the computations over the time. The proposed method is also validated through numerical simulations and hardware implementation.
Keywords: adaptive filtering; sliding window Wiener filter; Wiener-Hopf equation; recursive matrix inversion; RSC4BI; SWF